Prevalence and use of cannabis products and routes of administration among youth and young adults in Canada and the United States: A systematic review. (June 2022) - Wadsworth, Elle; Craft, Sam; Calder, Robert; Hammond, David
Graphical abstract: Highlights: 26 studies were reviewed on five modes of cannabis delivery and two cannabis products. Smoking cannabis had the highest prevalence rates among youth and young adults. Smoking rates appeared to reduce and vaping appeared to increase over time. The heterogeneity of cannabis use restricted our ability to collate average prevalence estimates. Abstract: Background: The current systematic review aimed to summarize the literature on the prevalence of routes of administration and cannabis products used among youth and young adults in Canada and the United States (US). Methods: Five academic databases were searched in April 2020 and February 2021. Peer-reviewed articles were included if they were a population-based quantitative observational study describing the prevalence of a cannabis product or route of administration among youth and young adults in Canada or the US. Risk of bias was assessed using Hoy and colleagues' risk of bias assessment tool. A narrative review was conducted. Results: Twenty-six studies were identified for the following routes of administration: smoking (n = 16), vaping (n = 21), dabbing (n = 3), oral (n = 13), topical (n = 1); and products: dried flower (n = 2), and concentrates (n = 8). Smoking had the highest prevalence rates among youth and young adults; however, rates of use appeared to reduce over time. Conversely, prevalence of vaping appeared to increase over time. Fewer studies focused on oral or dabbed cannabis but those that did reported prevalence estimates of approximately a third among recent cannabis consumers. Discussion: The heterogeneity of cannabis routes of administration restricted our ability to collate average prevalence estimates. In jurisdictions where non-medical cannabis is legal, policymakers should provide guidance and education to youth on each type of product and routes of administration. Other: Funding for this study was provided by a Canadian Institutes of Health Research (PJT-153342). The current review was registered with PROSPERO (CRD42020169275).